HUMAN CAPITAL DEVELOPMENT IN CENTRAL ASIAN COUNTRIES (British Journal of Global Ecology and Sustainable Development, 2025)
The development of human capital in the countries of Central Asia is a process that plays an important role in the economic, social and cultural development of the region. The concept of human capital is broad, combining factors such as knowledge, skills, health and employability of an individual. These factors play a key role in the sustainable development of countries, increasing their competitiveness and improving the quality of life of the population. The countries of Central Asia — Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan — pay great attention to the development of human capital. This process is being carried out in order to accelerate the economic growth rates of the region, ensure social stability and increase the well-being of the people.